Embedding QR codes in the teaching and learning process - Abby Ashraff Saprudin; Norlia Goolamally; Latifah Abdol Latif (2014)
The purpose of this action research is to explore the potentials of the Quick Response (QR) codes in mobile devices. In this research, QR codes and the smartphones are used as teaching tools in the classroom. Quick Response codes are two dimensional barcodes that are used to encode and decode information. These codes can contain information such as text, URL links, automatic SMS messages, or any other information that can be embedded in a two-dimensional barcode. This encoded data can be decoded by scanning the barcode with a mobile device that is equipped with a camera and QR reader software. The study setting was in an open distance learning institution and almost 95 % of the students in the classroom are working adults. Data were collected through observations and reflections from tutor and students. Almost 99% of the students have a smartphone which improves the reliability of implementing the research. Only one tutor volunteered to conduct the research using the QR codes. The tutor planned and prepared the appropriate content to be generated into the two dimensional barcodes. Students used their mobile phones to scan and decode the information embedded in the QR codes and class discussion continued from here on. Observations and reflections from tutor and the students are positive, suggesting that QR codes have the potential to be used in the teaching and learning process. (Abstract by authors)